Food Preference, Foraging Activity And Virtual Baiting Of The Forest Fire Ant, Tetraponera Rufonigra (JERDON) (Hymenoptera : Formicidae) - Sumino, Tomoki (2011)
This dissertation focuses on the feeding preference, foraging behavior, population estimation, as well as control of the forest fire ant, Tetraponera rufonigra (Jerdon). Among different types of lipid food provided, T. rufonigra preferred egg yolk the most (P < 0.05). However, they did not show any specific preference toward different choices of carbohydrate and proteinaceous foods that were provided (P > 0.05). When their most preferred food from each of the three food class was selected, they showed higher preference for carbohydrate-base food (sucrose) than those of protein-rich food (tuna) and lipid-base food (egg yolk) (P < 0.05).